2011
DOI: 10.1002/wcm.912
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shadow‐fading on QoS‐aware routing and admission control protocols designed for multi‐hop MANETs

Abstract: Providing quality‐of‐service (QoS) assurances in a mobile ad hoc network (MANET) is difficult due to node mobility, contention for channel access, a lack of centralised coordination, and the unreliable nature of the wireless channel. QoS‐aware routing (QAR) and admission control (AC) protocols comprise two of the most important components of a system attempting to provide QoS guarantees in the face of the above‐mentioned difficulties. This paper presents a comparative study, utilising a realistic shadow fading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…e most prominent ones include maintaining connection state, rapid allocation of resources, avoid scarcity of resources, and effectively manage dynamic topological changes caused due to mobility and appropriate resource reservation between the source and destination. ese challenges [7][8][9] has initiated the need to design and develop new QoS techniques [10][11][12][13] to support real-time data services in MANET. Furthermore, the new approach should be capable of differentiating various service requirements taking into consideration all other essential elements carefully with an ultimate goal to guarantee best end-to-end service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…e most prominent ones include maintaining connection state, rapid allocation of resources, avoid scarcity of resources, and effectively manage dynamic topological changes caused due to mobility and appropriate resource reservation between the source and destination. ese challenges [7][8][9] has initiated the need to design and develop new QoS techniques [10][11][12][13] to support real-time data services in MANET. Furthermore, the new approach should be capable of differentiating various service requirements taking into consideration all other essential elements carefully with an ultimate goal to guarantee best end-to-end service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, recent simulations [8], [9] and experimental [6] studies have clearly pointed out that shadow-fading is the crucial impairment to be considered for the analysis and design of protocols for cooperative wireless networks. In particular, in this context, including shadowing requires to carefully consider three fundamental issues:…”
Section: Introduction Automaticmentioning
confidence: 99%
“…In [6], authors Hanzo II and Tafazolli, proposes and evaluates new solutions for up the performance of QAR and AC protocols within the face of quality, shadowing, and ranging link SINR. it's found that proactively maintaining backup routes for active sessions, adapting transmission rates, and routing around quickly low-SINR links will perceptibly improve the dependability of assured turnout services.…”
Section: Literature Surveymentioning
confidence: 99%